Bitcoin and Web Search Query Dynamics: Is the price driving the hype or is the hype driving the price? - Bernd Süssmuth (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
Using a battery of timely multivariate time series techniques I study the Bitcoin cryptocurrency price series and web search queries with regard to their mutual predictability, Granger-causality and cause-effect delay structure. The Bitcoin is at first treated as a general currency, then as a generic asset. Google queries, although cointegrated, are found to be not helpful in predicting the USD exchange rate of Bitcoin as the speculative bubble in the latter antedates explosive behavior in the former. Chinese Baidu engine queries and compounded Baidu-Google queries predict Bitcoin price dynamics at relatively high frequencies ranging from two to five months. In the other direction, causality runs from the cryptocurrency price to queries statistics across nearly all frequencies. In both directions, the reaction time computed from a phase delay measure for the relevant frequency bands with significant causality ranges from slightly more than one month to about four months.
Keywords: C32; E32; E42; G12; G15; 330; Bitcoin; bubbles; frequency domain; causality